A Case Report on Rhinocerebral Mucormycosis of a Post COVID-19 Diabetic Patient (Bangladesh Journal of Medical Microbiology, 2021)
Mucormycosis is an invasive fungal infection caused by different saprophytic environmental fungus occurring predominantly among immunosuppressed patients. Coronavirus disease 2019 (COVID-19) itself and its treatment with immunosuppressive drugs and oxygen delivery systems are setting the scenes for opportunistic and co-infections with fungus. An elderly Bangladeshi woman with background of diabetes mellitus, hypertension and COVID-19, presented with the complaints of nasal obstruction, yellowish nasal discharge, hairing impairment and loosening of teeth. An early diagnosis combined with medical and surgical intervention can decrease mortality and morbidity. This is one of the few cases of post-COVID mucormycosis reported from Bangladesh.Bangladesh J Med Microbiol 2021; 15 (1): 26-29